2021
DOI: 10.15376/biores.16.2.4007-4020
|View full text |Cite
|
Sign up to set email alerts
|

Effect of activation temperature on properties of H3PO4-activated carbon

Abstract: The effects of different activation temperatures (Ta), ranging from 300 to 750 °C, on the ash content, yield, ignition point, microcrystalline structure, surface functional group, pore structure, and adsorption performance of activated carbon in preparing activated carbon by phosphoric acid (H3PO4) were systematically studied. The yield and volatile content of activated carbon decreased with the increase of Ta, while the ash content, ignition point, and graphitization degree showed the opposite results. The tu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 36 publications
(44 reference statements)
0
4
0
Order By: Relevance
“…KOH, as an activator, can react with some organic matter in AC pores to generate CO 2 and water, which is more conducive to the generation of new pores. [ 18 ]…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KOH, as an activator, can react with some organic matter in AC pores to generate CO 2 and water, which is more conducive to the generation of new pores. [ 18 ]…”
Section: Resultsmentioning
confidence: 99%
“…KOH, as an activator, can react with some organic matter in AC pores to generate CO 2 and water, which is more conducive to the generation of new pores. [18] In ZnCl 2 -activated AC, the NO concentration at the outlet of the AC-Z1 was the lowest at 2010 ppm under a steady state, and the denitration rate was only approximately 24.6%. An appropriate amount of ZnCl 2 can promote the release of volatiles, increase the surface micropores, and improve the adsorption capacity of AC.…”
Section: Denitration Performancementioning
confidence: 92%
“…Tembo et al (2017) reported that the CA content in juice samples was generally not strongly influenced by storage temperatures (freezing, 4, 6, 15, and 30 °C) for 60 days, and that the decrease in CA content was significantly lower (p ≤ 0.05) under refrigeration storage (6 °C) than at elevated temperatures (15 °C and 30 °C). The effects of temperature on the decomposition of disinfectant solutions vary; however, the concentration of active species in AA and PA solutions typically decreases, and their critical temperatures are 230 °C and 450 °C, respectively (Li et al, 2017;Joseph and White, 2021;Xu et al, 2021). H 2 O 2 , one of the most accessible disinfectants in various applications, has a limited stability, which markedly decreases the expiration period of a disinfectant (Madanská et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, compared with other current activators, H 3 PO 4 has the advantages of easy recycling and minimal environmental impact 26 , making it one of the most attractive activators for carbon materials. For example, using H 3 PO 4 at moderate temperature (350 °C), an AC with high surface area of 1547 m 2 /g was obtained from fir sawdust 27 ; also H 3 PO 4 was used to produce AC from a Douglas fir with a high surface area of 826.4-1726.5 m 2 /g. 26 Similarly, a high surface area of 2806 m 2 /g was obtained by preparing AC by chemical activation of paulownia wood with H 3 PO 4 .…”
Section: Introductionmentioning
confidence: 99%